Membrane structure and interactions with protein and DNA in bacteriophage PRD1. - Cockburn, J; Abrescia, N; Grimes, J; Sutton, G; Diprose, J; Benevides, J; Thomas, G; Bamford, J; Bamford, D; Stuart, D (2004)
Membranes are essential for selectively controlling the passage of molecules in and out of cells and mediating the response of cells to their environment. Biological membranes and their associated proteins present considerable difficulties for structural analysis. Although enveloped viruses have been imaged at about 9 A resolution by cryo-electron microscopy and image reconstruction, no detailed crystallographic structure of a membrane system has been described. The structure of the bacteriophage PRD1 particle, determined by X-ray crystallography at about 4 A resolution, allows the first detailed analysis of a membrane-containing virus. The architecture of the viral capsid and its implications for virus assembly are presented in the accompanying paper. Here we show that the electron density also reveals the icosahedral lipid bilayer, beneath the protein capsid, enveloping the viral DNA. The viral membrane contains about 26,000 lipid molecules asymmetrically distributed between the membrane leaflets. The inner leaflet is composed predominantly of zwitterionic phosphatidylethanolamine molecules, facilitating a very close interaction with the viral DNA, which we estimate to be packaged to a pressure of about 45 atm, factors that are likely to be important during membrane-mediated DNA translocation into the host cell. In contrast, the outer leaflet is enriched in phosphatidylglycerol and cardiolipin, which show a marked lateral segregation within the icosahedral asymmetric unit. In addition, the lipid headgroups show a surprising degree of order.